The Influence of Pocket Money, Gender, and Economics Track on Students' Financial Literacy: A Study of Senior High Schools in Bekasi Regency - Hellend Fransiska; Sri Indah Nikensari; Meta Bara Berutu (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The main objective of this study is to determine the influence of pocket money, gender, and economic track on the financial literacy of students at Senior High Schools in Bekasi Regency. Methodology: The methodology used is a quantitative approach. This research was only conducted in Tambun Utara District. The research sample consisted of 191 respondents, namely 11th-grade students majoring in the economics track. The data analysis techniques used in this study were instrument testing, analysis requirements testing, hypothesis testing using partial testing (t-test), and multiple linear regression analysis. Main Findings: The results of the tests conducted in this study indicate that pocket money has a positive and significant effect on financial literacy, gender has a positive but not significant effect on financial literacy, and economics track has a positive and significant effect on financial literacy. Novelty/Originality of this study: Although there are many studies on financial literacy, few have focused on the influence of the economics track among high school students, thus providing a new contribution that has not been explored before. This study involves quantitative data collected from 191 students at two schools in North Tambun District, thus providing a new perspective that has not been reported before.